Attitudes, practices and perceived barriers to hepatitis C screening among medical residents at a large urban academic medical center. Issue 11 (9th August 2019) - Winetsky, Daniel; Zucker, Jason; Carnevale, Caroline; Theodore, Deborah; Scherer, Matthew; Sani, Fereshteh; Elkington, Katherine; Cohall, Alwyn; Sobieszczyk, Magdalena E.; Gordon, Peter; Olender, Susan
Abstract: Infections with hepatitis C virus (HCV) are increasing among adolescents and adults born after 1965. Screening strategies may need to be adapted for this changing population. We surveyed trainees in different specialties about attitudes and practices related to HCV screening and identified specific barriers to screening across various healthcare settings. Constraints related to health system resources and the provider's role were among the most common barriers cited across specialties, but paediatrics residents also cited barriers specific to their population, which can likely be addressed with targeted education.